Mendorong Pengembangan Pariwisata: Wawasan Tata Kelola Desa di Bukit Lawang - Yanti, Dewi (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2024)
Bukit Lawang Plantation Tourism Village, situated in Bahorok District, Langkat Regency, North Sumatra, offers various engaging activities, including jungle trekking, rafting, bat cave tours, and tubing. The village government plays a pivotal role in the development and promotion of tourism within this area. This study aims to examine the village government's contributions to the growth of Bukit Lawang Plantation Tourism Village. Employing a qualitative research method with an interview approach, the study reveals several key findings. The village government has significantly enhanced community understanding of tourism and actively involves residents in decision-making processes. Promotional efforts through the village website have increased visibility and attraction. Furthermore, the government has provided essential facilities, contributing to the economic improvement of the community. It has also emphasized the preservation of cultural and environmental heritage, ensuring sustainable tourism practices. Additionally, the village government supports community participation in training programs, which aim to improve the quality of human resources, particularly in the tourism sector. These initiatives collectively foster a conducive environment for tourism development, driving local economic growth and cultural preservation. This study underscores the importance of local governance in transforming Bukit Lawang into a vibrant tourist destination, highlighting the multifaceted roles of the village government as a motivator, facilitator, and dynamic actor in the tourism sector.